THE IMPORTANCE OF PLAYFUL ACTIVITIES IN SPECIAL EDUCATION - Silva, Enoc José da; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
The article that is now presented is the result of bibliographical research, carried out from studies anchored in the scope of Special Education. Thus, we approach several ludic practices in special education with an emphasis on inclusion that facilitate work and perception, encouraging better learning in relation to the child who has learning difficulties. Therefore, this article aims to present the importance of playfulness in the teacher's work, as well as to show the importance of playfulness in teaching activities and its contributions to learning and the integral development of the student. We emphasize that it is of essential importance to understand that playing for children can be more than a daily activity, being a source of knowledge linked to their integral development. After all, while playing, the child pretends, imagines, frees himself, learns to control his aggression and overcome his fears. In this way, games can provide socialization and obedience to rules, in addition to facilitating mathematical logical reasoning. Therefore, it is of fundamental importance to use the ludic as a way of teaching, developing the best in the ability to absorb different contents in the child's daily life.